Semiconductor-laser fundamentals: Physics of the gain materials - Weng W, Chow (Springer, 2014)
This book presents an in-depth discussion of the semiconductor-laser gain medium. The optical and electronic properties of semiconductors, particularly semiconductor quantum-well systems are analyzed in detail, covering a wide variety of near-infrared systems with or without strain, as well as wide-gap materials such as the group-III nitride compounds or the II-VI materials. A wealth of examples for many different materials combinations bestow the book with quantitative and predictive value for a wide variety of applications.